Effect of Substrates Performance on the Microstructure and Properties of Phosphate Chemical Conversion Coatings on Metal Surfaces - Chunmiao Du; Kangqing Zuo; Zongliang Ma; Minru Zhao; Yibo Li; Shuai Tian; Yupeng Lu; Guiyong Xiao (Molecules, 2022)
Phosphate chemical conversion (PCC) technology has attracted extensive attention for its ability to regulate the surface properties of biomedical metals. However, titanium (Ti)-based alloys exhibit inertia because of the native passive layer, whereas zinc (Zn)-based alloys show high activity in acidic PCC solutions. The substrate performance affects the chemical reaction in the phosphating solution, which further leads to diversity in coating properties. In this work, the zinc-phosphate (ZnP) coatings are prepared on Ti alloy (TA) and Zn alloy (ZA) substrates using the PCC method, respectively. The coatings prepared herein are detected by a scanning electron microscope (SEM), X-ray diffractometer (XRD), laser scanning confocal microscope (LSCM), universal testing machine, contact angle goniometer, and electrochemical workstation system. The results show that the substrate performance has little effect on the phase composition but can significantly affect the crystal microstructure, thickness, and bonding strength of the coatings. In addition, the ZnP coatings improve the surface roughness of the substrates and show good hydrophilicity and electrochemical corrosion resistance. The formation mechanism of the ZnP coating is revealed using potential-time curves, indicating that the metal–solution interfacial reaction plays a dominant role in the deposition process.